Consumers’ intention towards online food ordering and delivery service / Nur Amanina Idris ... [et al.] - Idris, Nur Amanina; Mohamad, Mohamad Amiruddin; Manshoor, Amir; Mohamad, Norhaya Hanum; Che Ngah, Haslina (Universiti Teknologi MARA, Perlis, 2021)
Online food ordering and delivery services are the platforms that provide a system and service to the consumer to order and buy food products from foodservice or restaurant operators. The service is an up-and-coming trend among Millennials and the trend has ballooned with the introduction of movement control order (MCO) due to the pandemic COVID-19. The consumer’s demand towards online food ordering and delivery service has increased markedly due to the prohibition of dine-in at restaurant premises. This study focuses on highlighting the factors that influence consumer’s intention to use online food ordering and delivery services. The survey questionnaires were distributed among 384 respondents that represent the customers of restaurants in Shah Alam, Selangor. Data analyses were conducted using SPSS and multiple regression analysis. Findings revealed that usefulness, ease of use, and consumer’s enjoyment are the factors that influence consumer’s intention to use online food ordering services and conclusively, usefulness is the most significant factor that affects consumer’s intention to order food via online food ordering and delivery service. The findings from this study are beneficial for foodservice or restaurant operators in improving their businesses and staying competitive. Recommendations for future studies are included based on the findings of this study.